Benefício da revascularização do miocárdio em pacientes com disfunção ventricular e músculo viável: remodelamento ventricular reverso e prognóstico The beneficial effect of revascularization on patients with severe left ventricular dysfunction and viable myocardium: reverse remodeling and prognosis - Gustavo Calado de Aguiar Ribeiro; Ana Nunes; Fernando Antoniali; Mauricio Marson Lopes; Cledicyon Eloy da Costa (Brazilian Journal of Cardiovascular Surgery, 2005)
OBJETIVO: Analisar a importância da viabilidade do miocárdio e parâmetros clínicos na melhora da função ventricular, sintomas e prognóstico, como reversão do remodelamento. MÉTODO: Cento e quinze pacientes submetidos a revascularização do miocárdio com análise prévia da viabilidade do miocárdio com thallium-201. Fração de ejeção, volumes sistólicos e diastólicos do ventrículo esquerdo e classe funcional foram determinados, antes da cirurgia e a cada seis meses por 3 anos. RESULTADOS: Pacientes com > 4 segmentos viáveis demonstraram melhora da fração de ejeção de 34±6 para 44±4% (p<0,001), o volume diastólico foi de 113±31 para 91±22 ml/m² (p<0,001) e o volume sistólico foi 78,3±11 para 57±17 ml/m² (p<0,001). No grupo com < 4 segmentos viáveis, foi de 33,4±4 vs. 35,1±5% (p=0,19), o volume diastólico foi de 112±24 para 118±16 ml/m² (p=0,34), volume sistólico de 72±23 para 73±12 ml/m² (p= 0,81). Análise multivariada apontou fatores clínicos relacionados com evolução desfavorável (diabetes mellitus, mais que um infarto e longo intervalo de tempo entre infarto e operação). Melhora da classe funcional (NYHA) no grupo com mais segmentos viáveis e menor quantidade de eventos (log rank test, p = 0,0053). CONCLUSÃO: O benefício da revascularização, em pacientes com músculo viável, além da melhora função ventricular, proporciona remodelamento reverso, atenua a dilatação e reduz eventos. OBJECTIVES: To evaluate the integration of both viability and clinical parameters on the improvement in systolic performance, symptoms and prognosis, with post-revascularization reverse remodeling. METHOD: One hundred and fifteen patients underwent thallium-201 imaging before myocardial revascularization. Left ventricular ejection fraction, left ventricular end-systolic volume index and left ventricular end-diastolic volume index were determined before and at each 6 months post-revascularization for 3 years. RESULTS: Patients with > 4 viable segments on thallium-201 imaging demonstrated an improvement in left ventricular ejection fraction from 34±6 to 44±4%, p<0.001), left ventricular end-systolic volume decreased from 78.3±11 to 57±17 mL/m², p<0.001; left end-diastolic volume decreased from 113±31 to 91±22 ml/m², p<0.001). Patients with < 4 viable segments failed to demonstrate an improvement of the left ventricle ejection fraction, 33.4±4 vs. 35.1±5% (p=0.19), and exhibited ongoing left ventricle end-systolic remodeling, 72±23 vs. 73±12 mL/m² (p= 0.81), and the left ventricle end-diastolic volume increased from 112±24 to 118±16 mL/m² (p=0.34), without improvement in NYHA class, and worse long-term prognosis (event; log rank test, p=0.0053). The multivariable analysis demonstrated clinical variables related to the unfavorable evolution showed diabetes, more than one myocardial infarction, and time interval between myocardial infarction and surgery were associated with worse prognosis. CONCLUSION: The benefits of myocardium revascularization in patients with viable muscle, as well as an improvement in the left ventricular ejection fraction, provide reverse remodeling, improvement in functional class and favorable long-term prognosis.